Risks of exercise addiction and eating disorders among women attending fitness classes - O. V. Felsendorff; A. Y. Egorov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
This article discusses the risks associated with exercise addiction (sport addiction) and eating disorders among women participating in fitness classes. The sample consisted of 190 women assigned to an experimental group (N=114) and healthy control group (N=76) and were eligible for inclusion based on their frequency of class attendance. Participants completed a number of measures assessing the study variables including a specialized socio-demographic profile survey, the Exercise Addiction Inventory (EAI), and the Eating Attitude Test (EAT-26). Among those assigned to the experimental group, 13.15% were classified as at risk for exercise addiction with 16.6% of women at risk of an eating disorder. Group classification of the entire combined sample yielded three groups: (1) Non-Sports Addiction, (2) Sports Addiction Symptoms, and (3) At Risk Sports Addiction. Data analysis revealed a positive relationship between increased risk of sports addiction and increased risk of eating disorders. In general, this research suggests that women actively involved in fitness are at a higher risk of exercise addiction and eating disorders, providing evidence supporting the secondary nature of the sport addiction.